The Effect of Nutrition and Diet on the Causes of Kidney Failure in Minors in Indonesia - Erny Elviany Sabaruddin; Rival Pahrijal; Muhamad Ammar Muhtadi (West Science Interdisciplinary Studies, 2024)
Renal failure among minors in Indonesia has become a growing public health concern, with increasing evidence suggesting that dietary habits play a significant role in its development. This study investigates the influence of nutrition and diet on the causes of renal failure in minors, utilizing a quantitative analysis of 80 samples. Data were collected using a Likert scale (1 to 5) and analyzed with SPSS version 26. The results indicate significant positive correlations between the consumption of processed foods, sugary drinks, and the incidence of renal failure. Conversely, higher intake of fruits and vegetables was associated with a reduced risk of renal failure. Multiple regression analysis further confirmed the predictive power of these dietary factors, with processed foods and sugary drinks emerging as significant contributors to renal failure. The findings emphasize the need for targeted nutritional interventions and public health strategies to promote healthier eating habits among minors in Indonesia, aiming to reduce the incidence of renal failure and improve long-term health outcomes.